Validity and reliability of a physical activity questionnaire for Vietnamese adolescents - Hong Tang K; Trang Nguyen HHD; van der Ploeg Hidde P; Hardy Louise L; Dibley Michael J (BMC, 2012)
Abstract Background Accurate assessment of physical activity in adolescents at population level is necessary. In Vietnam, the International Physical Activity Questionnaire (IPAQ) and Physical Activity Questionnaire for Adolescents (PAQA) have been validated against accelerometers for use in adolescents. However, these questionnaires were originally designed for adults and showed poor validity. This study aims to assess the reliability and validity of the Vietnamese Adolescent Physical Activity Recall Questionnaire (V-APARQ). Methods One hundred and sixty five students were recruited from four junior high schools in Ho Chi Minh City Vietnam in 2004. V-APARQ asked students to report their usual organised and non-organised physical activity during a normal week and moderate- (MPA), vigorous- (VPA and moderate-to-vigorous- (MVPA) physical activity were calculated. Reliability was assessed by test-retest (2 weeks apart). Construct validity was assess by 7-day accelerometry, following the completion of the first V-APARQ. Results The construct validity of the V-APARQ showed Spearman correlation of 0.25 and 0.22 for the assessment of the questionnaire when compared to the accelerometer. Test-retest reliability showed a weighted Kappa of 0.75 and the intra-class correlation coefficient for MVPA was 0.57 for the whole group (MPA =0.37 and VPA = 0.62), and were higher in boys than girls. The Bland-Altman plots for reliability show a mean difference of 0.4 minutes (95 % CI = −3.2, 4.0) for daily MVPA (n = 146) and the limits of agreement were −42.6 to 43.4 mins/day. In boys MVPA was lower on the first, compared with second administration of V-APARQ while the reverse was observed among girls. Conclusion The reliability and validity of the V-APARQ were low to fair, but are comparable to other self-report physical activity questionnaires used among adolescents. V-APARQ will be useful for population monitoring of change in physical activity among urban Vietnamese adolescents.